The Profile of High-order Thinking Skills of Junior High School Students - Fery Joko Susilo; Budi Usodo; Dewi Sari (EDUPEDIA Publisher, 2023)
Industrial revolution 4.0 requires various parties to develop their potentials, including in education. Students' thinking skills and abilities become one of the aspects that underpin the accomplishment of educational goals. One of the abilities that students must develop is the ability to think at a higher level. In learning Mathematics, higher-order thinking skills are pivotal in the teaching and learning process. This research aims to analyze the higher-order thinking skills of seventh-grade students at SMP Baitul Qur'an Boarding School. This research employed mixed methods, which involved 204 students from 6 classes as research subjects. The instruments used were a test developed by considering three cognitive domains, including analyzing, evaluating, creating, and an interview sheet. The results revealed that students' performances in the three cognitive domains were still in an inadequate category with the following results; 27% for analyzing, 24% for evaluating, and 20% for creating. The utilization of learning resources that did not meet the standards contributed to students' poor performance in higher-order thinking skills.